Manajemen Wordpress untuk Menginformasikan Profil Dan Potensi Desa di Desa Gebang Kecamatan Teluk Pandan Kabupaten Pesawaran Lampung - Rahman Taufik; Wartariyus Wartariyus; Irwan Adi Pribadi; Muhaqiqin Muhaqiqin; Igit Sabda Ilman; Ridho Sholehurrohman (Universitas Teknokrat Indonesia, 2023)
According to the guidelines outlined in Law Number 6 of 2014 on the Regulation of Village Government Affairs, where the village is a legal community unit that has the authority to regulate and manage government affairs, the interests of the local community based on community initiative, original rights, and/or traditional rights that are recognized and respected in the NKRI government system. By utilizing information systems, it is not impossible for a village to create national economic power based on micro, small and medium enterprises, clean and transparent government, superior human resources, and a good social environment in the community. Based on discussions with Gebang village officials, on March 17, 2022 in the village hall, the problem currently experienced is how to introduce the profile and potentials that exist in Gebang village on a large scale (worldwide), by utilizing the current development of information systems, it is expected that the welfare of the Gebang village community in particular and the Pesawaran Lampung Regency community in general will increase. One of the current information system technologies is Wordpress. Wordpress is an application that can be used to build a website, which contains several functions/toolbars that can be used to create a website. With a website as an information system, Gebang village can introduce its profile and potentials on a large scale (worldwide). Therefore, it is necessary to understand the use of the Wordpress application for village officials, as an effort to introduce the profile and potentials that exist, in an effort to improve the welfare of the Gebang village community.